Luminescence properties, local symmetry and Judd–Ofelt analysis of a Sr2CaWO6:Eu3+, Na+ red phosphor. (17th June 2017) - Yang, Yang; Wang, Lei; Huang, Ping; Shi, Qiufeng; Tian, Yue; Cui, Cai'e
Graphical abstract: A series of red phosphors Sr2 CaWO6 :Eu 3+ and Sr2 CaWO6 :Eu 3+, M + (M = Li, Na, K) were synthesized by conventional solid-state reactions. After the introduction of charge compensators Na +, the intensity of the red emission band at 615 nm was about 43.4 times and 3.1 times stronger than Y2 O2 S:Eu 3+ under the 465 nm and 395 nm, respectively. Abstract: A series of red phosphors Sr2 CaWO6 :Eu 3+ and Sr2 CaWO6 :Eu 3+, M + (M = Li, Na, K) were synthesized by conventional solid-state reactions. The optical band gap was calculated through the UV-diffuse reflectance spectrum and strong CT band absorption was observed in compounds in the near ultraviolet region. The optimum doped concentration of Eu 3+ was determined to be 20 mol%, and the concentration quenching mechanism was found to be electric dipole–dipole interaction. After the introduction of charge compensators Na +, the intensity of the red emission band at 615 nm was almost three times than before and shows the strongest emission. Finally, the Ω λ ( λ = 2 and 4) intensity parameters was calculated according to Judd–Ofelt theory. The CIE colour co-ordinates of the Sr2 CaWO6 :Eu 3+, Na + was calculated ( x = 0.661, y = 0.339), which are close to NTSC standard values of primary red.